Natural and semi-synthetic insecticides protect onion from wireworms Agriotes spp. larvae (wireworm) damage - Prijović, Mirjana; Dervišević, Marina; Drobnjaković, Tanja; Stojanović, Luka; Miladinović, Vladimir; Ugrinović, Milan (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2025)
Wireworms, the larval stage of click beetles (Elateridae: Agriotes spp.), pose a significant threat to global agriculture, particularly to root vegetables, such as onion. Their subterranean lifestyle, as well as the withdrawal of some traditional synthetic insecticides, make them challenging to control. Therefore, this research aimed to compare the effects of natural, semi-synthetic and synthetic insecticides in controlling wireworm damage in an onion field. A field trial for testing the effects of different insecticidal treatments on plant density, wireworm damage (%) and total onion yield, was conducted at the Institute for Vegetable Crops (Smederevska Palanka, Serbia) in 2024. The experiment consisted of six treatments: an untreated control, three natural insecticides (two formulations of spinosad a.i. - granular and liquid, and Beauveria bassiana ATCC 74040 2.3×107 conidiospores/ml), a semi-synthetic insecticide (a.i. spinetoram) and a synthetic insecticide (a.i. tefluthrin). The insecticides were applied during planting, following their label application rates per hectare. Assessments were conducted 20 and 42 days after treatment (DAT) to determine plant density. Wireworm damage was specifically evaluated 42 DAT, and yield was calculated by weighing the harvested onion bulbs. The results showed that the granular spinosad formulation, applied in furrows at planting, significantly increased plant density 20 DAT, while its liquid formulation, applied as a soil treatment during planting, resulted in the lowest density. Spinetoram showed the highest plant density 42 DAT and the highest percentage of wireworm damage (15%) of all insecticides tested. The control had the highest percentage of damaged plants and the lowest yield. Onion yield was at the maximum after treatment with spinetoram, whereas the lowest yield was achieved after treatment with the granular spinosad formulation. Field trials show that natural and semi-synthetic insecticides can effectively control wireworms, ensuring adequate crop protection and viable yields. This study supports developing and adopting environmentally conscious soil pest management.